The Role of Intra-Campus Organizations in Improving Student's Soft Skills - Kunaenih; Suhari Muharam (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
Students, as the younger generation, not only create innovations but must also be able to form a quality personality to face the obstacles and challenges caused by the change itself. Through organizational activities, students can improve soft skills, especially public speaking skills, in developing their personality by implementing the Tri Dharma of Higher Education. This study aims to see what roles are presented by the intra-campus organization, namely the Islamic Religious Education Student Association, Jakarta Islamic University, as a forum for the process of students majoring in Islamic Education to improve the soft skills of Islamic Religious Education students. In this study, we used field research methods (field research) using a qualitative approach. This research was conducted at the Islamic University of Jakarta. In using the technique of determining the informant using snowball sampling, in collecting the required data, the researcher uses observation, interviews, and documentation. The results showed that the role of intra-campus organizations in improving the soft skills of Islamic Religious Education students at the Islamic University of Jakarta was for the intellectual development of students, fostering leadership, expanding networks or relationships, and fostering a sense of kinship, and could improve students' public speaking skills.